ANALISIS MASALAH PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 di TK ISLAM TERPADU YOGYAKARTA - Hana Ika Safitri (JIV-Jurnal Ilmiah Visi, 2022)
This study aims to descript the problem of online learning during the covid-19 pandemic at The Integrated Islamic Kindergarten Yogyakarta. The research method used in the research is a qualitative descriptive method. The study subjects were selected using a non-probability sampling technique that is purposive sample (selection of samples with certain considerations). The study subjects consisted of 4 teachers, 4 parents and 4 students. Data collection techniques used by researchers using data triangulation techniques. Data collection techniques used by researchers using questionnaires, interviews and literacy studies. The results showed that there are problems when applied online learning both experienced by parents, teachers, and children. Online learning problems experienced by parents such as: parents struggle to teach children to learn at home. Online learning problems experienced by teachers such as: lack of socialization related to online defense so that teachers have not fully mastered the technology that can support online learning. Online learning problems experienced by children during the covid pandemic such as: children feel bored and depressed when doing online learning at home with parents.